Evaluating active labor market programs in Romania - Núria Rodríguez-Planas; Jacob Benus (Institute for the Study of Labor (IZA), 2006)
We evaluate the presence of effects from joining one of four active labour market programs in Romania in the late 1990s compared to the no-program state. Using rich survey data and propensity score matching, we find that three programs (training and retraining, small business assistance, and employment and relocation services) had success in improving participants' economic outcomes and were cost-beneficial from society's perspective. In contrast, public employment was found detrimental for the employment prospects of its participants. We also find that there is considerable heterogeneity, which suggests that targeting may improve the effectiveness of these programs.
urn:nbn:de:101:1-2008060626
Keywords: 330; Arbeitsmarktpolitik; Wirkungsanalyse; Rumänien